Islamic banking system: the application and challenges from the Malaysian law perspective / Zanirah Mustafa@Busu ...[et al.]. - Mustafa @Busu, Zanirah; Mohamed, Abdul Majid Tahir; Awang@Ab Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah; Junoh, Noraini; Mat Jusoh, Nor Asmira; Ismail, Mohd Khairul Anuar; Nik Din, Nik Muniyati; Yusuf, Norazmila (2021)
The Islamic banking system in Malaysia has gone through continuous improvements from time to time. The system has been getting various recognitions besides serving as a reference to other countries. This study intended to highlight the extent to which the provisions of law for the Islamic banking system is implemented in Malaysia. According to the annual statistical reports, there were several cases in the courts relating to Islamic banking. This study aims to investigate the effectiveness of the law in handling this issue. The researcher will recommend suitable approaches that can be of benefit to responsible parties or certain bodies in ensuring that the Islamic banking system is Shariah compliance. This study will also provide an overview of the effectiveness of the current law in solving some of the issues related to the current Islamic banking system. The Islamic banking in Malaysia should be Shariah compliance in tern1s of the implementation and the practice of law in our nation.